KOMPETENSI SOFT SKILL GURU DI ERA PENDIDIKAN DIGITAL - Ismira; Firsty Sofila; Anita Ulpa; Roza Naulia Rosdianti; Nia Ikhtanova; Adellar Prasetya; Rahmatul Husna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The rapid development of digital technology has significantly transformed the educational landscape and reshaped the roles and competencies required of teachers. Beyond pedagogical and technological skills, teachers are increasingly demanded to possess strong soft skills to effectively manage learning processes in digital environments. This study aims to analyze and synthesize research findings related to teachers’ soft skill competencies in the era of digital education. The research employed a literature review method by examining relevant national and international journal articles, books, and conference proceedings published within the last decade. Data were collected through systematic searches in academic databases and analyzed using thematic analysis. The results indicate that essential soft skills for teachers in digital education include communication skills, adaptability, collaboration, creativity, emotional intelligence, digital ethics, and lifelong learning attitudes. These competencies play a crucial role in fostering meaningful interactions, managing virtual classrooms, and supporting students’ academic and socio-emotional development. The study concludes that strengthening teachers’ soft skills is a strategic necessity to enhance the quality of digital learning and recommends continuous professional development programs that integrate soft skill training with digital pedagogy.